IT auditing and application controls for small and mid-sized businesses : revenue, expenditure, inventory, payroll, and more - Wood, Jason, 1976-, author; Brown, William C., author; Howe, Harry, 1952-, author (Hoboken, New Jersey : John Wiley and Sons, Inc., 2013)
Includes bibliographical references (pages 399-403) and index